EKONOMI SYARIAH, MCDA-WDMA DAN PENTAHELIX COLLABORATION DI KOTA TASIKMALAYA - Arip Nugraha, Junjun (La Zhulma | Jurnal Ekonomi dan Bisnis Islam, 2025)
The limited integration of Islamic economic principles into Tasikmalaya City's planning documents poses a significant challenge, despite the city's strong demographic and Islamic cultural base. Policy fragmentation between the city and surrounding regions, along with weak municipal support, has hindered the development of a robust Islamic economic ecosystem. This study aims to formulate evidence-based strategic directions for Islamic economic development in Tasikmalaya.Using a mixed-methods approach with an exploratory sequential design within a Research and Development (R&D) framework, data were gathered from literature analysis, policy review, in-depth interviews, and structured questionnaires. The object of the study includes the institutional, stakeholder, and interactional dimensions of the Islamic economic ecosystem in Tasikmalaya City. The study identifies five key strategic priorities from twelve assessed variables using the MCDA-WDMA model: (1) intergovernmental policy synchronization, (2) strengthening Islamic economic institutions, (3) digital transformation of Islamic services, (4) community engagement through pesantren and Islamic organizations, and (5) fiscal incentives and affirmative regulation. Dynamic weight analysis from stakeholders reveals a dominant preference for Pentahelix collaboration. These findings confirm the utility of MCDA-WDMA in generating context-sensitive, evidence-based development frameworks.